Susceptibility to Default Training Options Across the Population - Lex Borghans; Bart H.H. Golsteyn (Institute for the Study of Labor (IZA), 2015)
This paper analyzes the tendency of people to choose default options when offered courses to acquire job related skills. We ask a random sample of Dutch people aged 6-80 which three skills are most important in their (future or past) jobs. Further on in the survey, we randomly select one of the skills the respondent indicated and (hypothetically) offer the respondent a course regarding this skill. The respondent can accept this offer, but can also exchange it for a course regarding one of the two other skills indicated. Our findings indicate that people generally have a strong tendency to choose the default option. This effect is similar across gender and education level. It appears that the effect of the default option is less strong around age 30 and declines after age 60.
Keywords: J24; J31; I2; 330; training; human capital; default option; experiment